Implementasi Manajemen Tenaga Pendidik dan Kependidikan di Sekolah Tinggi Teologi Simpson Ungaran - Maharin Maharin; Sri Ningsih; Sabda Budiman (Institut Agama Kristen Negeri Manado, 2021)
Management is a science that regulates the process of utilizing human resources effectively, and is also supported by other sources within the organization to achieve certain goals. To achieve development and progress in an institution, the implementation of human resource management, namely educators and education personnel, is important. Therefore, this study aims to determine how the implementation of the management of teaching and educational staff at Simpson Theological College. This research uses descriptive qualitative research method analysis to find out how the process carried out by the institution in the management of education and education personnel at the Simpson Theological College. The author uses data analysis through observation and interviews. The results of the data will be organized, then it is put together to be managed, the data obtained is then presented in descriptive form. The results of the study indicate: that the management process for educators and education is carried out through; Planning for the recruitment of educators and education personnel, organizing, coaching and developing, promoting and transferring educators and educational staff, then dismissing, compensation and awards for educators and education personnel. So the management is already in the implemented category. However, another explanation, especially the obstacles to funding the recruitment of educators is still lacking, due to human resources in addition to fulfilling the required criteria, as well as the interest and availability of human resources.